Analysis of Teacher’s Professional Allowance Relationships and National Exams - Wibowo, Adhi Prasetyo Satriyo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
The teacher professional allowance (TPG) is expected to improve the quality of national education, which refers to the National Education Standards (SNP), especially the graduation competency standards. The TPG budget tends to increase annually, but graduation competency standards tend to decrease. Therefore, this study aims to determine the relationship between teacher professional allowance and national examinations. The data used are secondary data consisting of the TPG budget and UN results. Teacher professional allowance budget from 2012–2018. The UN score is the average national aggregate UN score from 2012–2018. While the model used is the Pearson-Spearman correlation test, the results showed that the relationship between TPG and UN had a positive direction, but it was not significant.